2010
DOI: 10.1038/nbt.1653
|View full text |Cite
|
Sign up to set email alerts
|

Rapid profiling of a microbial genome using mixtures of barcoded oligonucleotides

Abstract: A fundamental goal in biotechnology and biology is the development of approaches to better understand the genetic basis of traits. Here we report a versatile method, trackable multiplex recombineering (TRMR), whereby thousands of specific genetic modifications are created and evaluated simultaneously. To demonstrate TRMR, in a single day we modified the expression of >95% of the genes in Escherichia coli by inserting synthetic DNA cassettes and molecular barcodes upstream of each gene. Barcode sequences and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
273
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(275 citation statements)
references
References 50 publications
2
273
0
Order By: Relevance
“…However, the precise relationship between aldehydes and ROS is unclear. For example, it was recently shown that resistance of E. coli to exogenous methylglyoxal is conferred by decreased expression of sodC (84). This is a surprising result given that sodC encodes a superoxide dismutase, which breaks down ROS (85).…”
Section: Addressing Aldehyde Toxicitymentioning
confidence: 99%
“…However, the precise relationship between aldehydes and ROS is unclear. For example, it was recently shown that resistance of E. coli to exogenous methylglyoxal is conferred by decreased expression of sodC (84). This is a surprising result given that sodC encodes a superoxide dismutase, which breaks down ROS (85).…”
Section: Addressing Aldehyde Toxicitymentioning
confidence: 99%
“…However, all genetic engineering methods share the same inherent problem: while they can alter a particular phenotype, they cannot simultaneously select for the most robust strain with that phenotype. Innovative screens, such as selection for colony size, have been developed that lessen the impact of this limitation, but the problem persists nevertheless (35,61). More critically, engineered alterations in one phenotype frequently come at the expense of other critical phenotypes, such as growth rate (39).…”
mentioning
confidence: 99%
“…Although our procedure requires RE manipulation, it is not limited by location, the availability of RE sites, nor addition of restriction site, but it is a rare occasion that a non-cutter can be useful. With the efficiency of targeting and the transient nature of tSM, it is conceivable that high throughput site-directed mutagenesis is possible to make a slight difference in otherwise identical plasmids, or by making random mutations in designated areas to generate pools of mutations in a defined domain [39] . Indeed, based on our experience, as long as homologous arms can form a stable complex with acceptor plasmids, single, double or even multiple mutations can be imported in one targeting event.…”
Section: Discussionmentioning
confidence: 99%